2019
DOI: 10.1021/acs.jpca.9b03157
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Empirical Double-Hybrid Functionals Trained against the GMTKN55 Database: revDSD-PBEP86-D4, revDOD-PBE-D4, and DOD-SCAN-D4

Abstract: We present a family of minimally empirical double-hybrid DFT functionals parametrized against the very large and diverse GMTKN55 benchmark. The very recently proposed ωB97M(2) empirical double hybrid (with 16 adjustable parameters) has the lowest WTMAD2 (weighted mean absolute deviation over GMTKN55) ever reported at 2.19 kcal/mol. However, refits of the DSD-BLYP and DSD-PBEP86 spin-component-scaled, dispersion-corrected double hybrids can achieve WTMAD2 values as low as 2.33 with the very recent D4 dispersion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
390
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 317 publications
(426 citation statements)
references
References 129 publications
(245 reference statements)
13
390
0
Order By: Relevance
“…For recent reviews of cWFT methods and their performance for the thermochemistry and thermochemical kinetics of organic molecules, see Karton 36 and Chan; 37 for a recent general review of both experimental and computational thermochemistry, see Ruscic and Bross. 38 One feature that cWFTs all share is the additivity approximation of the following form: with nearly 2500 main-group molecules, we found that the best DHDFT functionals, ωB97M(2) by Mardirossian and Head-Gordon 49 and revDSD-PBEP86-D4 by our group, 45 have WTMAD2 (weighted mean absolute deviation) statistics around 2.2 kcal/mol, competitive with or superior to the cWFT methods we tested. Needless to say, double hybrids are computationally much more economical, especially if RI (resolution of the identity) approximations 50−52 are applied.…”
Section: Introductionmentioning
confidence: 71%
“…For recent reviews of cWFT methods and their performance for the thermochemistry and thermochemical kinetics of organic molecules, see Karton 36 and Chan; 37 for a recent general review of both experimental and computational thermochemistry, see Ruscic and Bross. 38 One feature that cWFTs all share is the additivity approximation of the following form: with nearly 2500 main-group molecules, we found that the best DHDFT functionals, ωB97M(2) by Mardirossian and Head-Gordon 49 and revDSD-PBEP86-D4 by our group, 45 have WTMAD2 (weighted mean absolute deviation) statistics around 2.2 kcal/mol, competitive with or superior to the cWFT methods we tested. Needless to say, double hybrids are computationally much more economical, especially if RI (resolution of the identity) approximations 50−52 are applied.…”
Section: Introductionmentioning
confidence: 71%
“…For further details see Ref. 3 The primary metric and "objective function" employed is the WTMAD2 (weighted mean absolute deviation, type 2) as defined by Goerigk et al, defined as follows:…”
Section: Methodsmentioning
confidence: 99%
“…These authors covered a great many exchangecorrelation functionals, but a number of more recent ones such as ωB97M(2) 2 went unexplored for technical reasons. In addition, a set of revised 3 DSD double hybrids has meanwhile been fitted to GMTKN55, improving substantially on the original ones. 4 The purpose of the present short paper is to summarize these data and stress the strengths and weaknesses of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…[57] It was shown to be the most accurate and robust hybrid functional and a good alternative to double-hybrid functionals for large systems in recently performed benchmark studies that were the largest of their kind. [37,[58][59][60][61] Like other vander-Waals-DFT methods, only two-body contributions to the dispersion energy are included. As we are also interested in analysing potential non-additive three-body effects, we followed the example by Risthaus and Grimme [62] and enhanced the van-der-Waals-DFT type dispersion correction with the three-body term known from Grimme's DFT-D3 correction.…”
Section: Detailed Analysis Of Noncovalent Interactionsmentioning
confidence: 99%